Fluid mechanics and machinery - Ojha, C.S.P.; Berndtsson, R. (New Delhi Oxford University Press, 2010)
Fluid Mechanics and Machinery is designed to serve as a textbook for undergraduate and postgraduate students of mechanical and civil engineering. It will also be useful for students of electrical, aerospace, chemical, and production engineering.The book provides an exhaustive coverage of the essential concepts of the mechanics of fluids, both static as well as dynamic. In addition, it provides an overview of the design and operation of various hydraulic machines such as pumps and turbines.
Keywords: Mechanical Engineering